Tuberculosis as a Cause Enteroperitoneal Surgical Emergency in the National Hospital Dos de Mayo - Cataño Cauti, Eber (1998)
OBJECTIVES : To determine the characteristics of the enteroperitoneal TBC ( TBC- E) as a cause of surgical emergency. MATERIAL AND METHODS : Review of medical records of 40 patients operated at the Emergency Hospital Dos de Mayo with the diagnosis of TB -E ( 1990-1996 ) . RESULTS : The most affected age group was 21-30 years ( 45 % ) , predominantly male ( 62.5 %). History of pulmonary tuberculosis was found in 14 ( 35%). The clinical picture is characterized by abdominal pain ( 100 % ), nausea (77.5% ), vomiting (72.5% ) , abdominal distension (62.5 %) and abdominal wall resistance ( 55%). In E175 % compatible radiological pic-tures with pulmonary TB was found. The time of disease prior to surgery was less than a week in 67.5 %. 100% was laparotomized being most affected intestinal segments ileocecal and ileal (38.5% each). The pathology was ( +) in 17 of 30 samples ( 56.7 %). The postoperative hospitalization was less than a week at 55 %. 4 patients died ( 10%). CONCLUSIONS: TBC- E can cause acute surgical abdomen and should be considered in our hospitals emergencies .